Continuing chronic care services during a pandemic: results of a mixed-method study - Jennifer Sumner; Anjali Bundele; Lin Siew Chong; Gim Gee Teng; Yanika Kowitlawakul; Amartya Mukhopadhyay (BMC, 2022)
Abstract Background Patients with chronic diseases have seen unprecedented changes to healthcare practices since the emergence of COVID-19. Traditional 'on-site' clinics have had to innovate to continue services. Whether these changes are acceptable to patients and are effective for care continuation are largely unreported. Methods We evaluated the effectiveness of care provision at a re-structured chronic care clinic and elicited the patient experiences of care and self-management. We conducted a convergent, parallel, mixed-methods study. Adult patients attending a chronic care clinic were included. We extracted data from 4,849 clinic visits before and during the COVID-19 pandemic, including operational metrics and attendee profile. We also conducted fifteen interviews with patients from the same clinic using a semi-structured interview guide. Results Re-structuring the chronic clinic, including the introduction of teleconsultations, home-delivery of prescriptions and use of community-based phlebotomy services, served to maintain continuity of care while adhering to COVID-19 containment measures. Qualitatively, five themes emerged. Patients were able to adjust to healthcare practice changes and adapt their own lifestyles, although poor self-management practices were adopted. While most were apprehensive about attending the clinic, they valued ongoing care access and were reassured by the on-site containment measures. Conclusions Continuation of routine services is desired by patients and can be achieved through the adoption of containment measures, by greater collaboration with community partners, and the use of technology. Patients adapted to service changes, but poor self-management was evident. To prevent chronic disease relapse, services must strive to innovate rather than suspend services during pandemics.